The Eastern and Southeastern European countries in the pre-election programs of the key German parties 2017 - Froltsov, Vladislav V. (Journal of the Belarusian State University. International Relations, 2018)
The article considers the positions of six main political parties of Germany: CDU/CSU, SPD, FDP, Alliance 90 / The Greens, Left Party, AfD concerning German policy in Eastern and Southeastern Europe declared in their pre-election programs before the German Bundestag elections on 24 September 2017. A special attention is paid to their vision of Germany’s further relations with Russia and Turkey, as well as perspectives for a new EU enlargement in the East and Southeast directions. Based on a comparison of the contents of the pre-election programs in 2013 and 2017 the most important changes in the positions of all six parties regarding German interests and foreign policy priorities in the region are identified and characterized.
Keywords: German main political parties; pre-election programs; German foreign policy; Eastern and Southeastern Europe; Russia; Turkey; Enlargement of the European Union; Ukraine; Western Balkans countries; migration and visa policy